Diagnosing 0.1-10 Au Scale Morphology of the Fu Ori Disk Using Alma and Vlti/Gravity - Perez-Marquez, S (Institute of Physics Publishing, 2019)
We report new Atacama Large Millimeter/submillimeter Array Band 3 (86-100 GHz; ∼80 mas angular resolution) and Band 4 (146-160 GHz; ∼50 mas angular resolution) observations of the dust continuum emission toward the archetypal and ongoing accretion burst young stellar object FU Ori, which simultaneously covered its companion, FU Ori S. In addition, we present near-infrared (2-2.45 μm) observations of FU Ori taken with the General Relativity Analysis via VLT InTerferometrY (GRAVITY; ∼1 mas angular resolution) instrument on the Very Large Telescope Interferometer (VLTI). We find that the emission in both FU Ori and FU Ori S at (sub)millimeter and near-infrared bands is dominated by structures inward of ∼10 au radii. We detected closure phases close to zero from FU Ori with VLTI/GRAVITY, which indicate the source is approximately centrally symmetric and therefore is likely viewed nearly face-on. Our simple model to fit the GRAVITY data shows that the inner 0.4 au radii of the FU Ori disk has a triangular spectral shape at 2-2.45 μm, which is consistent with the H2O and CO absorption features in a 10-4 M o yr-1, viscously heated accretion disk. At larger (∼0.4-10 au) radii, our analysis shows that viscous heating may also explain the observed (sub)millimeter and centimeter spectral energy distribution when we assume a constant, ∼10-4 M o yr-1 mass inflow rate in this region. This explains how the inner 0.4 au disk is replenished with mass at a modest rate, such that it neither depletes nor accumulates significant masses over its short dynamic timescale. Finally, we tentatively detect evidence of vertical dust settling in the inner 10 au of the FU Ori disk, but confirmation requires more complete spectral sampling in the centimeter bands. © 2019. The American Astronomical Society. All rights reserved.